KEPATUHAN TATA KELOLA PERUSAHAAN DAN PERAN KOMISARIS INDEPENDENT PADA PERUSAHAAN KELUARGA DI INDONESIA - Rana Destalia; Mira Kartika Dewi Djunaedi (JURNAL LENTERA BISNIS, 2025)
This study aims to determine the compliance of family corporate governance in Indonesia and to see whether independent commissioners influences the compliance of family corporate governance. The population in this study were non-cyclical consumer sector companies listed on the Indonesia Stock Exchange in 2020-2022. The sample selection used the purposive sampling method. Based on the results of the Pooled OLS regression, it is known that family companies have a lower level of compliance than non-family companies and independent commissioners have an insignificant effect on the disclosure of corporate governance compliance.